2021
DOI: 10.1177/21582440211031552
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Engagement at the Northernmost University in the World

Abstract: Few studies have looked at the relationship of job characteristics and worker well-being among Norwegian academics. The main purpose of this study was to examine the relationship between job demands, job resources, burnout, and engagement among Norwegian university staff. In total, 236 staff from one university in Norway answered the questionnaire. Hierarchical multiple regression analyses identified job demands as the most important predictors for burnout. Autonomy was the most important job resource in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…It is notable that perceived mental health status was the strongest predictor of the total PWB level in the university staff. High job demands, insufficient resources, and poor staff management have consistently been associated with increased mental health issues of university staff (i.e., stress, anxiety, depression, and other mental health difficulties; Brewster et al, 2022; Kaiser et al, 2021). Therefore, it is essential to provide programs or resources for mental health support for university staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is notable that perceived mental health status was the strongest predictor of the total PWB level in the university staff. High job demands, insufficient resources, and poor staff management have consistently been associated with increased mental health issues of university staff (i.e., stress, anxiety, depression, and other mental health difficulties; Brewster et al, 2022; Kaiser et al, 2021). Therefore, it is essential to provide programs or resources for mental health support for university staff.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the COVID-19 pandemic has caused universities to experience higher turnover rates of 35% (Umpierrez, 2021). During the COVID-19 pandemic, approximately 80% of university employees reported higher levels of stress and feelings of anger associated with increased job demands and the deterioration of work-life balance (Kaiser et al, 2021). Student learning and university operations may be affected by increases in employee turnover and mental health issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific to academia, Kaiser et al (2021) observed a strong relationship between job demands and burnout in a sample of 236 employees at a Norwegian university, with autonomy being the most important resource for predicting commitment and reducing burnout. In addition, a study conducted with 300 employees of two international private universities in Thailand (Charoensukmongkol and Phungsoonthorn 2020a) while working remotely found that perceived uncertainties mediated the negative relationship between crisis communication and emotional exhaustion; informal communication may play a role in formal communication dynamics to reduce uncertainty during a crisis.…”
Section: Work From Homementioning
confidence: 99%
“…For instance, Course Hero reported that over half of their sample of 570 higher education faculty indicated feeling stressed, frustrated and emotionally burnt out and approximately 40% were contemplating leaving their positions (Renfrow, 2020). The data for college and university staff members parallels that of faculty (Irandoost et al ., 2021; Kaiser et al ., 2021). Thus, administrators should have a renewed focus on helping their employees manage their wellness.…”
mentioning
confidence: 99%